A130: Is the CCR5‐delta32 Mutation Protective Against Systemic‐Onset Juvenile Idiopathic Arthritis?. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Chasnyk, Vyacheslav; Fedorova, Elena; Egorov, Andrey; Ammosova, Tatiana; Nekhai, Sergei; Kostik, Mikhail; Santimov, Andrei; Dubko, Margarita; Kalashnikova, Olga; Masalova, Vera; Likhacheva, Tatyana; Snegireva, Ludmila; et al.
Abstract : Background/Purpose: The CCR5 protein is a chemokine receptor, and is known to be expressed on T cells, macrophages, dendritic and microglia cells. It is believed that different prevalence of HLA and CCR5‐ delta32—a 32 base pair deletion in the coding region—in various ethnic groups is associated with the severity and prevalence of chemokine‐mediated autoimmune diseases, systemic‐onset Juvenile Idiopathic Arthritis (soJIA) being among them (Del Rincon et al., 2003). Since the end of the last century the protective role of the CCR5‐delta32 mutation against JIA is discussed (Hinks et al., 2010), though it seems the role of this mutation is less simple than was hitherto thought. The purposes of the study was to compare the prevalence of the CCR5‐delta32 mutation in children with and without soJIA, to assess the association of this mutation with the severity of the disease and thus to evaluate its protective role. Methods: 234 children (193 of European origin, 25–Hispanic or Latino, 14–Afro‐Americans, 3–of Asian origin) with soJIA living in the USA and in the Northwestern part of Russia were enrolled in the study. Genomic DNA was isolated from blood samples using QIAamp Mini Kit and amplified by PCR. The following oligonucleotide primers were used to detect CCR5 d32: CCR5‐ Δ32‐F: 5′CTTCATTACACCTGCAGTC3′, CCR5‐Δ32‐R: 5′TGAAGATAAGCCTCACAGCC3′ by following condition: 95°–5′×1; 95°–15″→55°–15″→72°–60″×40; 72°–10′×3→4°–∞; the resulting PCR products were separated on 2% agarose gel by electrophoresis and visualized by Gel Doc XR Plus. Results: Mutation was revealed only in children of European origin. Though the prevalence of the heterozygous CCR5‐delta32 mutation being 16% and 21% in the USA and in Russia correspondingly didn't excel from its prevalence in populations in total (10–18% for Northwestern Russia, Kofiady, 2008; 11, 8%– for white American group, Downer et al, 2002), some laboratory and clinical signs of soJIA proved to be related to the mutation (see1 ). Heterozygous CCR5‐delta32 genotype was associated with milder so‐JIA course and predominance of the articular features over systemic. Conclusion: The results of the study may be considered rather not supporting the idea of the protective role of the CCR5‐delta32 mutation against soJIA, though the revealed associations—most of them related to the signs of the Macrophage Associated Syndrome—can be the basis for a more sophisticated research.